Ecological–Health Risk of Antimony and Arsenic in Centella asiatica, Topsoils, and Mangrove Sediments: A Case Study of Peninsular Malaysia - Yap, Chee Kong; Tan, Wen Siang; Cheng, Wan Hee; Syazwan, Wan Mohd; Azrizal-Wahid, Noor; Krishnan, Kumar; Go, Rusea; Nulit, Rosimah; Ibrahim, Mohd. Hafiz; Mustafa, Muskhazli; Omar, Hishamuddin; Chew, Weiyun; et al. (Frontiers in Environmental Science, 2022)
The current study assesed the ecological-health risks of potentially toxic arsenic (As) and antimony (Sb) in the vegetable Centella asiatica, topsoils and mangrove sediments sampled from Peninsular Malaysia. The As concentrations ranged from 0.21-4.33, 0.18-1.83, and 1.32-20.8 mg/kg dry weight, for the leaves, stems and roots of vegetable, respectively. The ranges of Sb concentrations were 0.31-0.62, 0.12-0.35, and 0.64-1.61 mg/kg dry weight, for leaves, stems and roots of vegetable, respectively. The children’s target hazard quotient (THQ) values indicated no non-carcinogenic risks of As and Sb in both leaves and stems, although children’s THQ values were higher than those in the adults. The calculated values of estimated weekly intake were lower than established provisional tolerable weekly intake of As and Sb for both children and adult consumers. The carcinogenic risk (CR) values of As for children’s intake of leaves and stems of vegetable showed more public concern than adults. The levels of Sb and As in the topsoils were generally higher (although not significantly) than those in the mangrove sediments, resulting in a higher geoaccumulation index, contamination factor and ecological risk, hazard index, THQ, and CR values. This indicated that the anthropogenic sources of Sb and As originated from the land-based activities before reaching the mangrove near the coast. The CR of As signifies a dire need for comprehensive ecological-health risks exposure studies, as dietary intake involves more than just vegetable consumption. Therefore, risk management for As and Sb in Malaysia is highly recommended.